Pengaruh Model Pembelajaran Berbasis Masalah Dapat Meningkatkan Kemampuan Belajar Siswa Kelas VI Pada Bidang Studi Pendidikan Kewarganegaraan MI Raudhatul Jannah Desa Ranggo Kecamatan Pajo Kabupaten Dompu Tahun Pelajaran 2019-2020 - Fitriani (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
In another formulation, it is stated that teaching is an attempt to organize a school environment to create conducive learning conditions for students. This formula is considered more advanced than the previous formula because it focuses more on the elements of students, the environment, and the learning process. Problem-based teaching is a teaching approach that uses real-world problems as a context for students to learn about critical thinking and problem-solving skills, as well as to acquire essential knowledge and concepts from the subject matter. This learning is used to stimulate higher-order thinking in problem-oriented situations including learning how to learn. The methods used in this research are (1) Observation Method, (2) Interview Method, (3) Documentation Method, and (4) Questionnaire Method. Based on the results of research on the teaching and learning process in the field of Civics studies in class VI MI Raudhatul Jannah, Ranggo Village, Pajo District, Dompu Regency, it can be concluded that 1. The effect of problem-based learning models in the Civic Education Field of Study can increase the learning independence of grade VI students at MI Raudhatul Jannah Ranggo Village, Pajo District, Dompu Regency, Academic Year 2019-2020. This can be seen from the increase in learning independence scores in the semester I and semester II. 2. The problem-based learning model in the Civics field of study can improve the learning independence of grade VI students of MI Raudhatul Jannah, Ranggo Village, Pajo District, Dompu Regency. This is evidenced by the increase in the scores of learning independence in semesters I and II. 3. The effect of the problem-based learning model can increase the learning independence and learning independence of class VI students of MI Raudhatul Jannah, Ranggo Village, Pajo District, Dompu Regency, 2019-2020 Academic Year